2006
DOI: 10.1038/sj.jid.5700456
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ferrochelatase Mutations in Japanese Patients with Erythropoietic Protoporphyria: High Frequency of the Splice Site Modulator IVS3–48C Polymorphism in the Japanese Population

Abstract: Table S1. Segregation analysis in family 1 of three microsatellite markers flanking KRT1 and the pathogenic mutation p.Phe191Ile demonstrating germline mosaicism. REFERENCESAlbers K, Fuchs E (1989) Expression of mutant keratin cDNAs in epithelial cells reveals possible mechanisms for initiation and assembly of intermediate filaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 6 publications
3
25
0
Order By: Relevance
“…In the second family, all three members having symptoms of EPP showed the C 683 →T mutation in combination with the trans IVS3-48C polymorphism. 17 These results from the analysis of two Japanese families indicated that the intronic IVS3-48C polymorphism in the non-mutated allele is a distinct determinant of the EPP phenotype. Their further investigation of the frequency of IVS-48C polymorphism in 104 Japanese controls revealed that the genotypic frequency of IVS3-48C/C was 0.192, that was over 10 times those of European countries (0-0.017).…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 91%
See 4 more Smart Citations
“…In the second family, all three members having symptoms of EPP showed the C 683 →T mutation in combination with the trans IVS3-48C polymorphism. 17 These results from the analysis of two Japanese families indicated that the intronic IVS3-48C polymorphism in the non-mutated allele is a distinct determinant of the EPP phenotype. Their further investigation of the frequency of IVS-48C polymorphism in 104 Japanese controls revealed that the genotypic frequency of IVS3-48C/C was 0.192, that was over 10 times those of European countries (0-0.017).…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 91%
“…17 Pedigree analysis of the other family members showed that the mother and two sisters, all asymptomatic, were heterozygous for this mutation. 17 Restriction fragment polymorphism analysis indicated that the proband was homozygous for the IVS3-48C polymorphism, while other family members, asymptomatic carriers, had a wild-type T at position IVS3-48 in trans to the mutated allele. 17 They concluded that the IVS3-48C polymorphism in one allele and a deleterious mutation (delCAA 853 ) in the other allele caused a phenotype of EPP.…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 99%
See 3 more Smart Citations